Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Motivasi Kerja Karyawan dalam rangka Pencapaian Target Pendaftaran Tanah Sistematis Lengkap (Studi Kasus Kantor Pertanahan Kabupaten Kebumen) - Arnowo, Hadi Arnowo (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2019)
Target achievement of Complete Systematic Land Registration in Kebumen Regency in 2017 as many as 50,000 fields have been completely completed (100%). The success is inseparable from the role of the leadership and employees of the Land Office of Kebumen Regency. The success of achieving the targets of Complete Systematic Land Registration activities (PTSL) is determined by employee motivation. Factors that play a role in employee motivation include the leadership style and organizational culture. Scientific Writing Research aims to determine the relationship between leadership style and organizational culture on employee work motivation associated with achieving PTS targets. The results of data processing using the correlation test show that there are significant influences and strong influences from each and collectively the factors of leadership style and organizational culture on the work motivation of the Kebumen Regency Land Office employees. This influence proves that the success of achieving the target activities must involve all elements of the employee to be responsible and professionally complete the task. The role of leaders in mobilizing and motivating employees is very important in order to create a positive organizational culture.